2020
DOI: 10.1111/iej.13398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the biological properties of two experimental calcium silicate sealers: an in vivo study in rats

Abstract: Aim To evaluate the biological properties of experimental sealers based on tricalcium silicate and dicalcium silicate, manipulated with polyethylene glycol (CE‐1) and with the addition of calcium hypochlorite (CE‐2) compared to AH Plus (AHP) and TotalFill BC Sealer (TBC). Methodology The tissue reaction caused by the materials in the subcutaneous tissue of rats was evaluated after implantation of polyethylene tubes filled with the materials at 7, 15, 30 and 60 days. Sections were stained with haematoxylin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…Moreover, the intense IL-6-immunoexpression point to a harmful effect of Calen on the connective tissue since IL-6 is a multifunctional pro-inflammatory cytokine, being considered an indicative parameter of the inflammatory reaction intensity 24 , 44 . Studies have shown a direct correlation between the reduction in the number of inflammatory cells and IL-6 immunoexpression in the capsules adjacent to the calcium silicate-based materials implanted in rat subcutaneous 23 , 24 , 27 , 45 . In the present study, the reduction in the immunoexpression of IL-6 was also accompanied by decrease in the number of inflammatory cells reinforcing the concept that this interleukin may modulate the inflammatory reaction in response to the endodontic materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the intense IL-6-immunoexpression point to a harmful effect of Calen on the connective tissue since IL-6 is a multifunctional pro-inflammatory cytokine, being considered an indicative parameter of the inflammatory reaction intensity 24 , 44 . Studies have shown a direct correlation between the reduction in the number of inflammatory cells and IL-6 immunoexpression in the capsules adjacent to the calcium silicate-based materials implanted in rat subcutaneous 23 , 24 , 27 , 45 . In the present study, the reduction in the immunoexpression of IL-6 was also accompanied by decrease in the number of inflammatory cells reinforcing the concept that this interleukin may modulate the inflammatory reaction in response to the endodontic materials.…”
Section: Discussionmentioning
confidence: 99%
“…In this standardized field (0.09 mm 2 ), the number of inflammatory cells (neutrophils, lymphocytes, plasma cells, and macrophages) was computed using the image analysis system. Thus, the number of inflammatory cells per millimetre square of capsule was obtained dividing the total number of inflammatory cells by the total standardized field of capsule 24 , 26 , 27 , 33 , 45 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term in vivo biocompatibility and toxicity of HiFlow should also be thoroughly studied before it is widely used in the clinic. Many previous studies have been performed to evaluate the in vivo biocompatibility of root canal sealers in a rat model of subcutaneous tissue implantation [ 4 , 14 ]. Therefore, the aims of the present study are to evaluate the reactions of subcutaneous connective tissues and organs to BC Sealer HiFlow and to compare them to the reactions to iRoot SP sealer and ProRoot mineral trioxide aggregate cement (MTA) (Dentsply, Tulsa, OK, USA), whose sufficient biocompatibilities have been confirmed by numerous in vivo and in vitro experiments [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%